Stability or growth: The rich nations' dilemma - Amar Nath Dutta (Intereconomics, 1976)
The article discusses the economic difficulties from which the industrialized nations have been suffering for the past years giving special regard to the controversy as to what concept of economic policy should be adopted in order to overcome the present problems.
Keywords: 330; Stabilisation Policy